Role of statins in the treatment of heart disease. Heart failure - Banach, Maciej; Okoński, Piotr (Przewodnik Lekarza/Guide for GPs, 2005)
Statins are the strongest hypolipeamic agents lowering cholesterol fraction LDL-C. Many clinical analyses proved that therapy with statins decreases the risk of coronary disease, death, stroke and arteriosclerosis of peripheral arteries. Benefits from statins administration were confirmed both in primary and secondary preventions, in men and women, in middle and old ages. The ability of statins to stabilization of atheromatous plaque and decreasing of coronary incidences occurrence in group of high risk patients ensures statin administration to be more common. Through the improvement of the endothelium function, anti-inflammatory and anti-cytokine characteristics and the improvement of neurohormonal balance and autonomic heart regulation (baroreceptors’ sensibility and variability of heart rhythm) may significantly influence on clinical course of heart failure contributing to the improvement of hemodynamic parameters of heart and inhibiting the progression of existing heart failure.